Movement and learning in the early years supporting dyspraxia (DCD) and other difficulties - Macintyre, Christine, 1938-; McVitty, Kim.; Sage eBooks (London : Paul Chapman, 2004)
Movement is the key in young children's development and it can affect how they learn and how they feel. Dyspraxia (CDC) is on the increase in young children, and less confident and competent movement can affect all aspects of their development.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Early childhood education -- Activity programs; Movement disorders in children; Movement education; Physical education for children with disabilities; Electronic books